(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The primary goal of this project is to learn and analyse the aerodynamic performance of wings and various types of winglets and wingtip devices. The objective of this study is to improve a model for various types of winglets and wingtip devices using the software SOLIDWORKS, And Fluent Analysis using the software ANSYS. The best performing aerofoil in terms of aerodynamic efficiency, NACA 64-215, was chosen for wing construction. A wing which is without winglets was simulated, followed by a wing with various winglets at different Cant angles. To determine the aerodynamic efficiency, a wing with a blended winglet and a raked winglet was simulated. In order to found a more efficient wing with winglets, designs of Blended and Raked winglets are modified, and comparison of the performance of winglets by varying with different cant angles, 30° and 60° were performed. As a result of this work, it was concluded that adding a winglet to a wing increases its aerodynamic efficiency in terms of CL/CD.